2022
DOI: 10.1002/adma.202202982
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐Broadband Strong Electromagnetic Interference Shielding with Ferromagnetic Graphene Quartz Fabric

Abstract: Flexible electromagnetic interference (EMI) shielding materials with ultrahigh shielding effectiveness (SE) are highly desirable for high‐speed electronic devices to attenuate radiated emissions. For hindering interference of their internal or external EMI fields, however, a metallic enclosure suffers from relatively low SE, band‐limited anti‐EMI responses, poor corrosion resistance, and non‐adaptability to the complex geometry of a given circuit. Here, a broadband, strong EMI shielding response fabric is demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(48 citation statements)
references
References 31 publications
0
48
0
Order By: Relevance
“…The advancement of gigahertz (GHz) band communication technologies has significantly brought convenience for humans, while it also leads to hazardous electromagnetic interference (EMI) or radiation. To this end, high-performance, easy-manufacturing, adjustable-performance, and low-cost EMI shields are urgently desired. , Since introducing micrometer-sized pores in EMI shields can facilitate multiple reflections of incident electromagnetic waves (EMWs) and effectively improve the EMI shielding effectiveness (SE), recently cellular foams/aerogels have attracted more and more attention for preparing high-performance EMI shields. However, compared with the bulk shields, the foam/aerogel-based shields generally suffer from fragility as well as poor flexibility . This limits the development of high-performance EMI shields demanding good mechanical toughness, flexibility, and even stretchability, which are especially desired for next-generation flexible devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advancement of gigahertz (GHz) band communication technologies has significantly brought convenience for humans, while it also leads to hazardous electromagnetic interference (EMI) or radiation. To this end, high-performance, easy-manufacturing, adjustable-performance, and low-cost EMI shields are urgently desired. , Since introducing micrometer-sized pores in EMI shields can facilitate multiple reflections of incident electromagnetic waves (EMWs) and effectively improve the EMI shielding effectiveness (SE), recently cellular foams/aerogels have attracted more and more attention for preparing high-performance EMI shields. However, compared with the bulk shields, the foam/aerogel-based shields generally suffer from fragility as well as poor flexibility . This limits the development of high-performance EMI shields demanding good mechanical toughness, flexibility, and even stretchability, which are especially desired for next-generation flexible devices.…”
Section: Introductionmentioning
confidence: 99%
“…7−10 However, compared with the bulk shields, the foam/aerogel-based shields generally suffer from fragility as well as poor flexibility. 11 This limits the development of high-performance EMI shields demanding good mechanical toughness, flexibility, and even stretchability, which are especially desired for nextgeneration flexible devices. The hydrogels, composed of a cellular structure filled with plenty of water and a network of cross-linking hydrophilic building blocks, can reveal satisfactory mechanical flexibility, elasticity, toughness, fatigue resistance, and especially stretchability.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical work reported that the magnetic property of N-doped Ti 3 C 2 MXene can be affected by the concentrations and the distributions of nitrogen . It has been reported that nitrogen doping is a promising approach to induce the basal-plane localized magnetic moments in graphene nanosheets. , Liu et al reported that the control of the graphitic N-doping configuration endows graphene coatings with high magnetic responsiveness, thus leading to the synergistic effect of EMI shielding and EM wave absorption. N-containing Ti 3 CNT x films have also been demonstrated with magnetic properties at lower temperatures .…”
Section: Introductionmentioning
confidence: 99%
“…26 Although the horizontal graphene film can be transformed into a thick three-dimensional (3D) structure, such as using textile substrates, the thickness of the composite film would unavoidably increase to the millimeter scale. 27,28 Owing to the lightweight, porous structure, and high conductivity that cause the tuning of relative permittivity and favors impedance matching, 14 vertical graphene nanowalls (VGNs) have been taken into consideration. Composed of vertically aligned few-layer graphene flakes, VGNs maintain the fantastic electrical properties of graphene.…”
Section: Introductionmentioning
confidence: 99%
“…The total EMI SE (SE T ) was smaller than 5 dB in the X-band for the few-layer thick graphene films . Although the horizontal graphene film can be transformed into a thick three-dimensional (3D) structure, such as using textile substrates, the thickness of the composite film would unavoidably increase to the millimeter scale. , …”
Section: Introductionmentioning
confidence: 99%